SKINFOLD THICKNESS IN MEN WITH VARIOUS FORMS OF ECZEMA - Аль-Омарі Ала’а Осама Ахмад; Dmytrenko, S.V.; Chaika, V.H.; Isakova, N.M.; Gunas, I.V. (World of Medicine and Biology, 2021)
The study analyzed the differences in the skinfold thickness between healthy and/or eczema patients depending on the severity of the disease. It was found that most indicators of skinfold thickness (except for folds on the side) in men with different forms and severity of eczema has significantly less value than in healthy men. Between patients with true and/or microbial eczema of varying severity, only isolated differences in the skinfold thickness were found. Identified differences in the skinfold thickness can be used to predict the phenotypic manifestation of eczema.